1994
DOI: 10.2105/ajph.84.4.543
|View full text |Cite
|
Sign up to set email alerts
|

The report of the Surgeon General: preventing tobacco use among young people.

Abstract: This year's surgeon general's report on smoking and health is the first such report to focus on young people. From extensive data that indicate that tobacco use is a pediatric epidemic, the report reached six major conclusions: (1) Nearly all first use of tobacco occurs by age 18. (2) Most adolescent smokers are addicted to nicotine. (3) Tobacco is often the first drug used by young people who subsequently use illegal drugs. (4) There are identified psychosocial risk factors for the onset of tobacco use. (5) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
121
0
12

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(138 citation statements)
references
References 40 publications
5
121
0
12
Order By: Relevance
“…Preventing this morbidity and mortality is a clear public health priority. Because most smokers start smoking during adolescence 7, 8, and initiating alcohol consumption at a young age is a strong risk factor for dependence in later life 9, it is crucial to identify avoidable risk factors for tobacco or alcohol use in this period of development.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing this morbidity and mortality is a clear public health priority. Because most smokers start smoking during adolescence 7, 8, and initiating alcohol consumption at a young age is a strong risk factor for dependence in later life 9, it is crucial to identify avoidable risk factors for tobacco or alcohol use in this period of development.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that having family or peers that smoke will increase the likelihood of ever smoking [62,63]. Furthermore, epidemiological studies suggest that adolescents are more vulnerable to nicotine addiction: 88% of smokers tried their first cigarette before age 18, and the development of daily cigarette smoking typically occurs before age 25 [10,41]. There is also considerable evidence that genetics influence several smoking-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…14 A adição à nicotina ocorre com o uso regular de tabaco e adolescentes fumantes têm alta probabilidade de tornarem-se adultos fumantes. 3 Os fatores de risco para tabagismo na adolescência citados na literatura são: sexo e idade, nível socioeconômico, fumo dos pais ou irmãos e dos amigos, rendimento escolar, trabalho remunerado e separação dos pais. Os estudos mostram que o hábito de fumar dos amigos e dos irmãos mais velhos está fortemente associado ao tabagismo em adolescentes.…”
Section: Introductionunclassified